A BLOC-1 Mutation Screen Reveals that PLDN Is Mutated in Hermansky-Pudlak Syndrome Type 9 - Cullinane, Andrew R. (Elsevier, 2011)
Hermansky-Pudlak Syndrome (HPS) is an autosomal-recessive condition characterized by oculocutaneous albinism and a bleeding diathesis due to absent platelet delta granules. HPS is a genetically heterogeneous disorder of intracellular vesicle biogenesis. We first screened all our patients with HPS-like symptoms for mutations in the genes responsible for HPS-1 through HPS-6 and found no functional mutations in 38 individuals. We then examined all eight genes encoding the biogenesis of lysosome-related organelles complex-1, or BLOC-1, proteins in these individuals. This identified a homozygous nonsense mutation in PLDN in a boy with characteristic features of HPS. PLDN is mutated in the HPS mouse model pallid and encodes the protein pallidin, which interacts with the early endosomal t-SNARE syntaxin-13. We could not detect any full-length pallidin in our patient's cells despite normal mRNA expression of the mutant transcript. We could detect an alternative transcript that would skip the exon that harbored the mutation, but we demonstrate that if this transcript is translated into protein, although it correctly localizes to early endosomes, it does not interact with syntaxin-13. In our patient's melanocytes, the melanogenic protein TYRP1 showed aberrant localization, an increase in plasma-membrane trafficking, and a failure to reach melanosomes, explaining the boy's severe albinism and establishing his diagnosis as HPS-9.